2023
DOI: 10.1093/ced/llad135
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of topical corticosteroid use in dermatophytosis: a cost-of-illness analysis of steroid-modified vs. steroid-naive dermatophytosis

Abstract: Dermatophytosis is one of the leading causes of visits to the Dermatology department, especially in India, where the hot and humid climate favours fungal acquisition and perpetuation. Usual modalities of treatment include the use of either oral or topical antifungals or a combination of both, depending upon the severity and extent of infection as well as the type of causative organism. But lately, steroid-modified dermatophytosis, an iatrogenically perpetuated dermatophytosis caused by the indiscriminate use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It should also have potent anti-inflammatory action, minimal adverse events, low cost, and be safe to use in pregnancy and lactation, as well as renal and hepatic failure. Treatment modalities include oral or topical antifungals or a combination of both, depending on the severity and extent of infection, as well as the type of the culprit fungi [ 3 ]. Combinations of various antifungal groups should be used to prevent resistance from emerging.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It should also have potent anti-inflammatory action, minimal adverse events, low cost, and be safe to use in pregnancy and lactation, as well as renal and hepatic failure. Treatment modalities include oral or topical antifungals or a combination of both, depending on the severity and extent of infection, as well as the type of the culprit fungi [ 3 ]. Combinations of various antifungal groups should be used to prevent resistance from emerging.…”
Section: Treatmentmentioning
confidence: 99%
“…In India, a recent analysis of treatment costs showed that patients who use topical steroids spend 40% more on treatment than those who do not use steroids. This was true for both patients who had never used steroids before and those who had used them in the past [ 3 ]. The epidemiology of dermatophytosis in India indicates that the high temperatures and humidity prevalent in the region promote the acquisition and perpetuation of fungal infections.…”
Section: Financial Considerationsmentioning
confidence: 99%
See 1 more Smart Citation